(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This present study also identifies the prevalence of anaemia, its risk factors, and the consequences, both physical and mental, that are cognitive and academic, in adolescents. For this purpose, a sample of 1,000 adolescents is taken, and the prevalence is analyzed according to gender and income groups, the correlation of iron intake with anaemia, and the correlations of anaemia withspecific health outcomes related to adolescents. The results showed that adolescents from middleincome group have the highest percentage of anaemia prevalence. Also, in our data set, there was no statistically significant association between iron intake and anaemia status or with health outcomes. In all, the findings of this study underline that anaemia in adolescents is a significantpublic health problem that can only be effectively and appropriately tackled with specific interventions and policies, which are nutritional education, routine screening, and socioeconomic assistance.